2017
DOI: 10.1038/am.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

A novel biodegradable self-healing hydrogel to induce blood capillary formation

Abstract: A major challenge in tissue engineering is to generate a functional microvasculature that ensures proper blood perfusion and connection with surrounding tissues. Strategies such as the incorporation of growth factors have been proposed to induce the growth of new blood vessels into engineered tissue, but limitations remain. Herein a novel chitosan-fibrin (CF)-based self-healing hydrogel with a modulus of~1.2 kPa was developed. The self-healing hydrogel was found to be injectable and to degradẽ 70% in 2 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 56 publications
0
89
0
Order By: Relevance
“…For example, they could be transplanted with biomaterials into patients with limb ischemia or coronary artery disease to repair the damaged blood circulation system. A very recent study has explored that single dispersed ECs seeded in the chitosan‐fibrin‐based (CF) self‐healing hydrogel could grow into spheroids and form capillary‐like structures . In addition, the injection of the CF hydrogel alone could rescue the blood circulation in limb ischemic mice.…”
Section: Applications Of Substrate‐derived Spheroids In Tissue Regenementioning
confidence: 99%
See 1 more Smart Citation
“…For example, they could be transplanted with biomaterials into patients with limb ischemia or coronary artery disease to repair the damaged blood circulation system. A very recent study has explored that single dispersed ECs seeded in the chitosan‐fibrin‐based (CF) self‐healing hydrogel could grow into spheroids and form capillary‐like structures . In addition, the injection of the CF hydrogel alone could rescue the blood circulation in limb ischemic mice.…”
Section: Applications Of Substrate‐derived Spheroids In Tissue Regenementioning
confidence: 99%
“…A very recent study has explored that single dispersed ECs seeded in the chitosan-fibrin-based (CF) self-healing hydrogel could grow into spheroids and form capillary-like structures. [61] In addition, the injection of the CF hydrogel alone could rescue the blood circulation in limb ischemic mice. Thus, the hydrogel which promotes the spheroid formation of ECs and tube formation may offer new possibilities for future applications to vascular repair.…”
Section: New Blood Vessel Formation and Cell Spheroidsmentioning
confidence: 99%
“…These outcomes may be attributed to the lack of bio-functionality in the networks of current self-healing hydrogels, which is critical in cell-material interactions, cell responses and morphogenesis [4448]. Most recently, Hsu’s group developed a composite self-healing hydrogel cross-linked by chitosan and formylbenzoic-functioned poly (ethylene glycol) [76]. The fibrin was introduced into the network to provide bio-functional sites for inducing blood capillary formation.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the mechanical properties of chemically crosslinked hydrogels, researchers have developed ingenious strategies, including nanocomposite hydrogels, double-network hydrogels, hybrid crosslinking hydrogels and tetra-polyethylene glycol hydrogels. [14][15][16][17][18][19][20][21][22] Recently, increasing research attention has been dedicated to enhancing the mechanical performance of physically crosslinked supramolecular hydrogels. One recent study demonstrated very tough physical hydrogels composed of polyampholytes.…”
mentioning
confidence: 99%